Withdrawal of antihypertensive medication in young to middle-aged adults: a prospective, single-group, intervention study - Hae-Young Lee; Kyoung Suk Lee (BMC, 2023)
Abstract Background Although antihypertensive drug therapy is commonly believed to be a life-long therapy, several recent guidelines have suggested that antihypertensive medications can be gradually reduced or discontinued for some patients whose blood pressure (BP) is well-controlled for an extended period. Thus, this pilot study aimed to describe the success rate of antihypertensive drug discontinuation over 6 months among young and middle-aged patients with hypertension. Methods This was a prospective, single-group, intervention study. Patients were eligible for inclusion if their cardiologist judged them to be appropriate candidates for this study, their BP had been controlled both in the office (< 140/90 mmHg) and 24-h ambulatory BP monitoring (< 135/85 mmHg) for at least 6 months with a single tablet dose of antihypertensive medication. A total of 16 patients withdrew their antihypertensive medications at baseline after they received the education, and were followed up over 6 months. After the follow-ups, six patients participated in the in-depth interview. Results The likelihood of remaining normotensive at 30, 90, 180, and 195 days was 1.00, 0.85, 0.51, and 0.28, respectively. There were also no significant differences in baseline characteristics and self-care activities over time between normotensive (n = 8) and hypertensive groups (n = 8). In the interview, most patients expressed ambivalent feelings toward stopping medications. Psychological distress (e.g., anxiety) was the primary reason for withdrawal from this study although the patients' BP was under control. Conclusions We found that only a limited portion of antihypertensive patients could stop their medication successively over 6 months. Although we could not identify factors associated with success in maintaining BP over 6 months, we believe that careful selection of eligible patients may increase success in stopping antihypertensive medications. Also, continuous emotional support might be essential in maintaining patients' off-medication.